Using a multiple water balance approach to estimate recharge for the optimum mine, Mpumalanga - Van Wyk, Morne (University of the Free State, 2018)
This dissertation focused on using multiple water balance recharge methods within rehabilitated opencast mines at the Optimum Coal Mine, Mpumalanga,for the aim that a combination of water balance methods will yield more conclusive recharge from rainfall values within spoil material. It is known that different recharge methods yield very different results concerning recharge. New recharge methods were implemented based on the data received from the mine and compared to the recharge method already developed and proven to work. In the pursuit to solve the complicated issue of calculating recharge from rainfall, four newly formulated methods were produced, called the Rainfall Infiltrated Volume, Stage Curve Volume, Dry and Wet Calculations and Recharge from Stage Curve Volume. These methods were compared to wellknown recharge methods which included the Saturated Volume Fluctuation, Cumulative Rainfall Departure and Water Table Fluctuation methods over a fiveyear period. These methods, combined, narrowed the range between the minimum and maximum recharge values, usually estimated for the study area, and in the process provided a better understanding of the water management systems in this area. Pit Volume Calculations yielded a 25% void space for spoils, which were used in the recharge calculations. Each method yielded a minimum and maximum recharge value from rainfall, but not all of them produced the results expected from the area. The Zevenfontein opencast rehabilitated pit produced very accurate and believable recharge from rainfall at 18–20% for the new recharge methods and 15–17% for the known recharge methods. The Optimus opencast rehabilitated pit had numerous problems, but in the end also produced believable results at 25–30% for the new recharge methods and 15–20% for the known recharge methods. Thus, it was concluded that a combination of recharge methods yielded more conclusive recharge values.
Dissertation (M.Sc.Agric. (Institute for Groundwater Studies))--University of the Free State, 2018
Keywords: Optimum; Coal; Recharge; Water balance methods; Pit calculations; Rainfall infiltrated volume; Stage curve volume; Dry calculations; Wet calculations; Saturated volume fluctuation; Cumulative rainfall departure; Water table fluctuation; Void space; Pumping cycles; Pumping rates; Water levels